2011
DOI: 10.1007/s11084-011-9239-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic effects of Murchison Material: Prebiotic Synthesis and Degradation of RNA Precursors

Abstract: Mineral components of the Murchison meteorite were investigated in terms of potential catalytic effects on synthetic and hydrolytic reactions related to ribonucleic acid. We found that the mineral surfaces catalyzed condensation reactions of formamide to form carboxylic acids, amino acids, nucleobases and sugar precursors. These results suggest that formamide condensation reactions in the parent bodies of carbonaceous meteorites could give rise to multiple organic compounds thought to be required for the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…These data are of particular interest providing the first example on the catalytic effect of a meteorite on the synthesis of nucleic bases ( Fig. 2 and Scheme 1 pathway "L") [96].…”
Section: Syntheses Of Nucleic Bases From Formamidementioning
confidence: 94%
See 2 more Smart Citations
“…These data are of particular interest providing the first example on the catalytic effect of a meteorite on the synthesis of nucleic bases ( Fig. 2 and Scheme 1 pathway "L") [96].…”
Section: Syntheses Of Nucleic Bases From Formamidementioning
confidence: 94%
“…From the one-carbon atom formamide the RNA precursors are simply obtained by warming at 160 • C [80,96] or by decreasing the temperature while providing part of the energy in the form of UV radiation [81,82]. These synthetic reactions occur in the presence of any one of the following common terrestrial minerals: calcium carbonate, zeolite, alumina, titanium oxides, clays, olivines, phosphates (reviewed in [27,80]), and of iron-sulphur-copper minerals [87], zirconium minerals [89], borates [93]; or, from outer environments, in the presence of Murchison meteorite minerals [96].…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, Saladino, Di Mauro, and coworkers (14) proposed that the parent molecule for the one-pot synthesis of nucleobases is formamide (15)(16)(17)(18)(19)(20)(21)(22)(23). Their team, together with other authors, demonstrated the formation of (not only) fundamental nucleobases for the origin of RNA in experiments involving the heating of formamide in presence of manifold catalysts (17,(24)(25)(26), upon UV irradiation (27), proton (28) and heavy-particle radiation (29), exposition to shock waves (18), etc. Recently, Hörst et al (30) also referred to a positive result on qualitative detection of RNA nucleobases and manifold amino acids from tholines created in a N 2 , CH 4 , CO mixture.…”
mentioning
confidence: 99%
“…Evidence of the catalytic properties of meteorites in prebiotic chemistry was recently provided by thermal processes of condensed-phase FA at relatively high temperatures (333 and 413 K) (57,58) or at the most extreme temperature conditions modeling impact events in Earth's atmosphere or surface (3,59). During their wandering, meteorites are exposed, under an extreme variety of temperature conditions, to ionizing radiation of cosmic origin (60) able to excite and dissociate FA (the ionization energy of the FA being ∼11-15 eV).…”
mentioning
confidence: 99%